Educating everybody's children : diverse teaching strategies for diverse learners : what research and practice say about improving achievement - ASCD Improving Student Achievement Research Panel; Cole, Robert W.; Association for Supervision and Curriculum Development (Alexandria, Va. : Association for Supervision and Curriculum Development, 1995)
"Educating Everybody's Children encapsulates what research has revealed about successfully addressing the needs of students from economically, ethnically, culturally, and linguistically diverse groups and identifies a wide range of effective principles and instructional strategies. Although good teaching works well with all students, educators must develop an extensive repertoire of instructional tools to meet the varying needs of students from diverse backgrounds. Those tools and the knowledge base behind them are the foundation of this revised and expanded second edition of Educating Everybody's Children. Each strategy discussed in the book includes classroom examples and a list of the research studies that support it. The most important thing we have learned as a result of the education reform movement is that student achievement stands or falls on the motivation and skills of teachers. We must ensure that all teachers are capable of delivering a standards-based curriculum that describes what students should know and be able to do, and that these standards are delivered by means of a rich and engaging "pedagogy of plenty". By these two acts we can ensure that all schools will be ready and able to educate everybody's children.
Includes bibliographical references
Keywords: Education -- United States -- Experimental methods; Educational equalization -- United States; Minorities -- Education -- United States; Children with social disabilities -- Education. -- United States; Academic achievement -- United States; Multicultural education -- United States